Carnitines slow down tumor development of colon cancer in the DMH‐chemical carcinogenesis mouse model. Issue 7 (9th May 2013) - Roscilli, Giuseppe; Marra, Emanuele; Mori, Federica; Di Napoli, Arianna; Mancini, Rita; Serlupi‐Crescenzi, Ottaviano; Virmani, Ashraf; Aurisicchio, Luigi; Ciliberto, Gennaro
Abstract Dietary agents are receiving much attention for the chemoprevention of cancer. While curcumin is known to influence several pathways and affect tumor growth in vivo, carnitin and its congeners play a variety of important metabolic functions: are involved in the oxydation of long‐chain fatty acids, regulate acyl‐CoA levels and influence protein activity and stability by modifying the extent of protein acetylation. In this study we evaluated the efficacy of carnitines in the prevention of cancer development using the 1, 2, ‐dimethylhydrazine (DMH)‐induced colon carcinogenesis model. We also assessed whether their combination was able to give rise to increased protection from cancer development. Mice treated with DMH were dosed orally with curcumin and/or carnitine and acylcarnitines for 20 weeks. At the end of the treatment colon samples were collected, and scored for multiple ACF and adenomas. We observed that carnitine and acyl‐carnitines had same, if not higher, efficacy than curcumin alone in inhibiting the formation of neoplastic lesions induced by DMH treatment. Interestingly, the combination of curcumin and acetyl‐L‐carnitine was able to fully inhibit the development of advanced adenoma lesions. Our data unveil the antitumor effects of carnitines and warrant additional studies to further support the adoption of carnitines as cancer chemopreventative agents. J. Cell. Biochem. 114: 1665–1673, 2013. © 2013 Wiley Periodicals, Inc.